Product Defect Detection using Image Template Matching with MATLAB - Abdillah, Muhammad Hasya; Sabilah, Muhammad Arip Putra; Suherman, Andika; Astharini, Dwi (EXSACT-A, 2023)
Abstract— In industrial manufacturing processes, ensuring the quality of products is crucial. This paper proposes a system for detecting defects in products using image template matching techniques implemented in MATLAB. The system's primary function is to compare captured images of products with predefined templates to identify potential defects accurately. The method employed in this system is template matching, a well-established approach in image analysis that allows for efficient defect detection. MATLAB, a widely used software tool for image processing, provides the necessary functionality and a robust set of algorithms to implement the proposed system. The experimental results demonstrate the effectiveness of the approach in detecting various types of defects, such as scratches, cracks, and misalignments. This defect detection system offers a reliable and automated solution for improving the efficiency and productivity of manufacturing industries. By enabling early detection and intervention, it contributes to enhancing product quality control and minimizing defective outputs, ultimately leading to cost savings and customer satisfaction. Keywords— Defect Detection; MATLAB; Template Matching; Image Processing